PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN, AUDIT TENURE DAN REPUTASI AUDITOR TERHADAP OPINI AUDIT MODIFIKASI GOING CONCERN - Frans Guntara Ardi; Indra Saputra; Susi Dwi Mulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This study uses one research model to obtain empirical evidence about the effects of financial distress, company size, audit tenure and auditor reputation on going concern modified audit opinion. Variables used in this research model are going concern modified audit opinion, financial distress, company size, audit tenure and auditor reputation. Research samples consists of listed manufacture companies in Indonesian Stock Exchange in the period of 2013 – 2015. Based on sample picked with purposive sampling method, samples which used in this research is 32 companies wih three years period resulting 96 sample units. Data analysis conducted with logistic regression method ananlysis with SPSS bersion 23.0, with significance value set at 5%. The results of the research concludes that financial distress and auditor reputation has significant effect on going concern modified audit opinion. Meanwhile, company size and audit tenure does not have significant effect on going concern modified audit opinion.